Some population characteristics and viability of captive Asian elephant (Elephas maximus) in Thailand - MANANYA PLA-ARD; RONGLARP SUKMASUANG; SUWIMOL UTHAIRASMEE (Society for Indonesian Biodiversity, 2022)
Abstract. Pla-ard M, Sukmasuang R, Uthairasmee S. 2022. Some population characteristics and viability of captive Asian elephant (Elephas maximus) in Thailand. Biodiversitas 23: 1072-1081. Sustaining long-term viable populations of captive Asian elephants poses a challenge in managing the existing populations. Therefore, studies of the characterization and long-term persistence of the population are an important aspect of the action. The results of long-term population analysis of captive Asian elephants (Elephas maximus Linnaeus, 1758) using Population Viability Analysis (PVA) from the demography information showed that the birth and reproductive rate of the captive elephants in Thailand are declining significantly while the mortality rate trends are stable. Analysis results of the population's ability to persist in the long term from the initial population of 4,252 elephants, it was found that extinction of the population if the percentage adult female breeding is 80%, which is the best-case scenario, if the mortality rate increases by 6% from the present, the population will start going into extinction. If the percentage adult female breeding is set to 2.3%, which is the lowest breeding condition in captive Asian elephants, the population will become extinct in every scenario. Therefore, the most important method in maintaining the captive Asian elephant population is to increase the birth rate improve the well-being, health, nutrition, environment, and welfare of elephants in captivity are important factors that would reduce deaths and are very important for the long-term survival of the population in Thailand.